Piezoelectric MEMS Resonators - Bhugra, Harmeet; Piazza, Gianluca; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book introduces piezoelectric microelectromechanical (pMEMS) resonators to a broad audience by reviewing design techniques including use of finite element modeling, testing and qualification of resonators, and fabrication and large scale manufacturing techniques to help inspire future research and entrepreneurial activities in pMEMS. The authors discuss the most exciting developments in the area of materials and devices for the making of piezoelectric MEMS resonators, and offer direct examples of the technical challenges that need to be overcome in order to commercialize these types of devices. Some of the topics covered include: Widely-used piezoelectric materials, as well as materials in which there is emerging interest Principle of operation and design approaches for the making of flexural, contour-mode, thickness-mode, and shear-mode piezoelectric resonators, and examples of practical implementation of these devices Large scale manufacturing approaches, with a focus on the practical aspects associated with testing and qualification Examples of commercialization paths for piezoelectric MEMS resonators in the timing and the filter markets ...and more! The authors present industry and academic perspectives, making this book ideal for engineers, graduate students, and researchers.
AIN Thin Film Processing and Basic Properties -- Lead Zirconate Titanate (PZT) for M/NEMS -- Gallium Nitride for M/NEMS -- Lithium Niobate for M/NEMS Resonators -- Quality Factor and Coupling in Piezoelectric MEMS Resonators -- Flexural Piezoelectric Resonators -- Laterally Vibrating Piezoelectric MEMS Resonators -- BAW Piezoelectric Resonators -- Shear Piezoelectric MEMS Resonators -- Temperature Compensation of Piezo-MEMS Resonators -- Computational Modeling Challenges -- Fabrication Process Flows for Implementation of Piezoelectric MEMS Resonators -- Reliability and Quality Assessment (Stability and Packages) -- Large Volume Testing and Calibration -- High Frequency Oscillators for Mobile Devices -- BAW Filters and Duplexers for Mobile Communication. .
Keywords: Electronics; Microtechnology; Microelectromechanical systems; Nanotechnology; Optical materials; Electronics and Microelectronics, Instrumentation; Microsystems and MEMS; Nanotechnology; Optical Materials